I like it elegant: imprinting personalities into product shapes. Issue 1 (2nd January 2020) - Prieto, Pablo; Briede, Juan C.; Beghelli, Alejandra; Canessa, Enrique; Barra, Carlos
ABSTRACT: The ability of designing personality-based products is key for their successful launch in the market, since customers prefer products that have a similar personality to their own. However, the creative process designers use to imprint a given personality into a product is still a 'black-box' and lengthy process that requires expertise and successive customer validation. The research challenge here is how to systematize the creative process of defining new geometries of a product with an intended personality. Due to the complexity of this challenge, the focus of this paper is solely about the process of defining the shape of a product with a given personality. A 5-step systematic method to extract and define the key form aspects of a specific personality is defined to do this. The use of the method is exemplified by developing a shape which is representative of an elegant personality and its suitability is tested using questionnaires answered by both design and non-design trained people. Results show that customers better recognize the personality imprinted on the object when the steps of the proposed method are fully complied with. This work will assist designers with the creative process of product form definition.